Community policy model in preventing pedophilia crimes in the community on an ongoing basis from the perspective of community citizenship policy - Bayu Suseno; M Mustofa; Puspitasari Puspitasari; Ricardi S. Adnan (Universitas Negeri Yogyakarta, 2026)
This study was prompted by the alarming prevalence of sexual violence against children in Indonesia and the continued dominance of repressive approaches in dealing with pedophilia crimes. Historically, public policy responses have focused excessively on criminalisation and law enforcement, with the police as the main actor. This study uses a qualitative approach based on a literature review, utilising the interactive analysis model includes data reduction, conceptual data display, and conclusion drawing through cross-source verification. The findings indicate that addressing the multidimensional complexity of pedophilia requires a preventive governance structure involving six key sectors ( hexahelix model): the government acts as a regulator and legal supervisor; academics providing an evidence-based foundation through empirical research; the business sector contributing with technological innovations for protection and corporate social responsibility (CSR); the media shaping public opinion and conducting educational campaigns; communities acting as agents of daily social supervision and early detection; and civil society organizations (CSOs) focusing on policy advocacy and victim mediation. Optimising this cross-sector collaboration effectively builds a strong social ecosystem grounded in citizen responsibility, the core values of Pancasila, and the strengthening of participatory social control. In addition, this study proposes a practical, operational syntax structured into five integrated stages to ensure the systematic implementation and sustainability of the model. This research contributes to the conceptual and practical development of civic education as a preventive public policy tool, grounded in active citizen participation, to create an environment that protects children.